Third-Order Differential Subordination Features of Meromorphic Functions: Erdelyi–Kober Model Integral Operator Application - Ibrahim S. Elshazly; Borhen Halouani; Rabha M. El-Ashwah; Alaa H. El-Qadeem; Gangadharan Murugusundaramoorthy (Axioms)
This study is concerned with the class of p-valent meromorphic functions, represented by the series <semantics>f(ζ)=ζ−p+<msubsup>∑k=1−p∞</msubsup>dkζk</semantics>, with the domain characterized by <semantics>0<|ζ|<1</semantics>. We apply an Erdelyi–Kober-type integral operator to derive two recurrence relations. From this, we draw specific conclusions on differential subordination and differential superordination. By looking into suitable classes of permitted functions, we obtain various outcomes, including results analogous to sandwich-type theorems. The operator used can provide generalizations of previous operators through specific parameter choices, thus providing more corollaries.